Conservação in vitro de mangabeira nativa da Região Nordeste do Brasil - Santos, Micaele da Costa (2010)
Mangaba tree (Hancornia speciosa Gomes) is a tropical fruit found in different regions of the country, being more abundant in areas of coastal tablelands and lowlands of Northeast region, where it is explored in an extractive way and it is suffering an accelerated process of erosion genetics. The development of methods for conservation of genetic resources still available it is essential. This work aimed at improving technical and scientific in vitro conservation by slow growth of mangaba tree. The work was done at the Laboratory of Plant Tissue Culture of Embrapa Coastal Tablelands. To evaluate the effect of sucrose and sorbitol nodal segments were inoculated in test tubes with 25 mL of MS medium supplemented with 1 mg.L-1 of indol acetic acid (IAA) and 1 mg.L-1 of benzylaminopurine (BAP) and different sorbitol concentrations (10; 20 and 40 g.L-1) combined with 0 and 15 g.L-1 of sucrose. To evaluate the effect of abscisic acid (ABA) and the recipient and sealing types, nodal segments were inoculated in "mayonnaise" flasks and in test tubes with 25 mL of MS medium supplemented with 30 g.L-1 of sucrose, containing 0 or 0.5 mg.L-1 of ABA combined with plastic lid and aluminum foil. To study the effect of the mannitol and cultivation time two mangaba accessions were inoculated on MS medium supplemented with 0; 5; 10; 15 and 20 g.L-1 of mannitol. The proline quantification was done in mangaba microcuttings from conservation medium containing 10 and 20 g.L-1 of sorbitol. In the recovery stage of the growth explants conserved in vitro for 120 days, in the previous experiments were inoculated on MS medium and the viability of crops evaluated at 30 and 60 days. It is feasible to maintain nodal segments in the absence of sucrose in the presence of 10 or 20 g.L-1 of sorbitol and nodal segments in the presence of 0.5 mg.L-1 of ABA in test tubes sealed with aluminum foil lid for 120 days. It is possible the conservation of seedlings germinated in vitro in MS culture medium with 15 and 20 g.L-1 of mannitol for 180 days. Larger proline accumulation is observed in stem than in leaves of mangaba tree. Explants maintained in the presence of 10 g.L-1 of sorbitol and sucrose absence and in the presence of 0.5 mg.L-1 of ABA at conservation present higher viability in the growth recovery.